Phylogenetic relationships among species of Tigriopus (Multicrustacea: Copepoda: Harpacticoida) with comments on its biogeography - NAZARI, FATEMEH; GÓMEZ, SAMUEL (Zootaxa, 2022)
Here we present some hypothetical phylogenetic relationships and the evolutionary history of the harpacticoid copepod genus Tigriopus Norman, 1869 using morphological data. Cladistic analyses were performed with 21 morphological characters, including 15 ingroup and eight outgroup species. Inferred topology from Bayesian inference supported the monophyletic status of the genus, and revealed two main evolutionary lineages. One of these lineages (the brachydactylus-iagi lineage) comprises species from the Indo-Pacific, the northern Pacific, the southern Pacific, and the southern Atlantic; it is supported by the tetrasetose female P5 endopod. The fulvus-angulatus lineage is composed of three clusters with species from the north Atlantic and the Mediterranean Sea (the fulvus-brevicornis clade), the northwestern Pacific and the Indo-Pacific (the japonicus-sirindhoranae clade), and from the southern Pacific, the Indian Ocean, and the Southern Ocean (the crozettensis-angulatus clade). The groundpattern of the mandibular basis of the fulvus-angulatus lineage seems to include a bisetose mandibular basis, and, the presence of three setae on this segment in the japonicus-sirindhoranae clade is interpreted here as a character reversal. Biogeographic analyses suggest that the tropical Indo-Pacific region is the most probable ancestral area of the genus that diversified through vicariance events.